PENDEKATAN INOVATIF DALAM MENINGKATKAN MANAJEMEN MUTU BERBASIS SEKOLAH - Muaddyl Akhyar; Zulfani Sesmiarni; Ramadhoni Aulia Gusli; Muhammad Afif Al Faruq (LP2M IAIN Sultan Amai Gorontalo, 2025)
The main objective of this research is to analyze and evaluate the innovative approaches applied in improving school-based quality management at SMPN 1 VII Koto Sungai Sariak. This research uses a qualitative approach with a case study method to explore in depth the application of innovative approaches in improving school-based quality management at SMPN 1 VII Koto Sungai Sariak. The case study was chosen to contextually understand the specific dynamics that occur in this school, focusing on innovative management practices. The results of this study show that SMPN 1 VII Koto Sungai Sariak implements an innovative and adaptive school-based quality management model by involving all stakeholders in decision-making. Although the use of technology in learning provides benefits, challenges such as limited infrastructure and teacher skills still exist. The principal's visionary leadership and community support are supporting factors while resistance to change and limited resources are barriers. The school creates a conducive educational environment through transparency and teacher training, but for sustainability, more investment in technology infrastructure and collaboration with external parties is needed.